Warming Up to New Possibilities with the Capsaicin Receptor TRPV1: mTOR, AMPK, and Erythropoietin - Maiese, Kenneth (Current Neurovascular Research, 2017)
Background: Transient receptor potential (TRP) channels are a superfamily of ion channels termed after the trp gene in Drosophila that are diverse in structure and control a wide range of biological functions including cell development and growth, thermal regulation, and vascular physiology. Of significant interest is the transient receptor potential cation channel subfamily V member 1 (TRPV1) receptor, also known as the capsaicin receptor and the vanilloid receptor 1, that is a non-selective cation channel sensitive to a host of external stimuli including capsaicin and camphor, venoms, acid/basic pH changes, and temperature. Methods: Given the multiple modalities that TRPV1 receptors impact in the body, we examined and discussed the role of these receptors in vasomotor control, metabolic disorders, cellular injury, oxidative stress, apoptosis, autophagy, and neurodegenerative disorders and their overlap with other signal transduction pathways that impact trophic factors. Results: Surprisingly, TRPV1 receptors do not rely entirely upon calcium signaling to affect cellular biology, but also have a close relationship with the mechanistic target of rapamycin (mTOR), AMP activated protein kinase (AMPK), and protein kinase B (Akt) that have roles in pain sensitivity, stem cell development, cellular survival, and cellular metabolism. These pathways with TRPV1 converge in the signaling of growth factors with recent work highlighting a relationship with erythropoietin (EPO). Angiogenesis and endothelial tube formation controlled by EPO requires, in part, the activation of TRPV1 receptors in conjunction with Akt and AMPK pathways. Conclusion: TRPV1 receptors could prove to become vital to target disorders of vascular origin and neurodegeneration. Broader and currently unrealized implementations for both EPO and TRPV1 receptors can be envisioned for for the development of novel therapeutic strategies in multiple systems of the body.
Keywords: autophagy